Extraintestinal manifestations of Crohn's disease: difficulties in diagnosis - A. Yu. Davydova; R. V. Repnikova (Фундаментальная и клиническая медицина)
Inflammatory bowel disease, a group of inflammatory conditions of the colon and small intestine, principally includes ulcerative colitis and Crohn's disease. Current attention to inflammatory bowel disease is promoted by worldwide increase in its incidence and morbidity as well as shortcomings of existing treatment. Extraintestinal (musculoskeletal, skin, renal, hepatic etc.) manifestations of inflammatory bowel disease significantly complicate the diagnosis and may predict the development of intestinal symptoms. In certain cases, the severity of extraskeletal manifestations may exceed that of the main diagnosis. Here we describe a clinical example of this scenario.